2006
DOI: 10.1016/j.yqres.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Great earthquakes of variable magnitude at the Cascadia subduction zone

Abstract: Comparison of histories of great earthquakes and accompanying tsunamis at eight coastal sites suggests plate-boundary ruptures of varying length, implying great earthquakes of variable magnitude at the Cascadia subduction zone. Inference of rupture length relies on degree of overlap on radiocarbon age ranges for earthquakes and tsunamis, and relative amounts of coseismic subsidence and heights of tsunamis. Written records of a tsunami in Japan provide the most conclusive evidence for rupture of much of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
149
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 52 publications
9
149
0
Order By: Relevance
“…Understanding tsunami-induced sediment movement is also extremely important for tsunami geologists who have made significant effort to estimate the tsunami heights, flow depths and velocities by establishing qualitative relationships between tsunami deposits and tsunami hydrodynamic characteristics (Jaffe and Gelfenbuam, 2007;Moore et al, 2007;Morton et al, 2008;Spiske et al, 2010). The information derived by inverse modeling from paleo-tsunami deposits, can further help us understand tsunami sources and attendant tectonic character of a particular region in some detail (Bourgeois, 2009;Martin et al, 2008;Nelson et al, 2006). However, the inverse modeling faces great challenges since sediment movement is highly depended on tsunami wave form, bathymetry and topography near shoreline and sediment sources.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding tsunami-induced sediment movement is also extremely important for tsunami geologists who have made significant effort to estimate the tsunami heights, flow depths and velocities by establishing qualitative relationships between tsunami deposits and tsunami hydrodynamic characteristics (Jaffe and Gelfenbuam, 2007;Moore et al, 2007;Morton et al, 2008;Spiske et al, 2010). The information derived by inverse modeling from paleo-tsunami deposits, can further help us understand tsunami sources and attendant tectonic character of a particular region in some detail (Bourgeois, 2009;Martin et al, 2008;Nelson et al, 2006). However, the inverse modeling faces great challenges since sediment movement is highly depended on tsunami wave form, bathymetry and topography near shoreline and sediment sources.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, almost all palaeoseismic records of subduction earthquakes have been obtained from the coastal zone (e.g. Atwater 1987;Darienzo et al 1994;HemphillÁHaley 1995;Nelson et al 1996Nelson et al , 2006Zachariasen et al 1999;Sawai et al 2002;Nanayama et al 2003;Cisternas et al 2005;Melnick et al 2006;Rajendran et al 2008). Within the coastal zone, sea level can be used as a benchmark against which uplift and subsidence of the upper plate due to subduction earthquake deformation can be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the Kuril Islands Tsunami with a 1 m tsunami runup and a limited inundation zone did not pass the preservation threshold in the Hawaiian high-energy beach sites. Nelson et al (2006) further suggest that depositional sites must favor preservation for a tsunami event to leave a geologically identifiable trace. Clearly, the Hawaiian beach facies studied does not constitute a positive preservation regime.…”
Section: Quantitative Assessmentmentioning
confidence: 97%
“…The positive correlation appears to be in large part controlled by a similar geologic setting of the sites and reflect the impact of changes in climate and sea level. Based upon studies in Cascadia, Nelson et al (2006) suggested that there are thresholds for creating and preserving evidence of earthquakes and tsunami. Clearly, the Kuril Islands Tsunami with a 1 m tsunami runup and a limited inundation zone did not pass the preservation threshold in the Hawaiian high-energy beach sites.…”
Section: Quantitative Assessmentmentioning
confidence: 99%